2021
DOI: 10.1007/s10570-021-03997-2
|View full text |Cite
|
Sign up to set email alerts
|

Active antibacterial coating of cotton fabrics with antimicrobial proteins

Abstract: The prevention of bacteria colonization by immobilizing proteins with antimicrobial activity onto cotton fabrics was investigated. Such coatings have potential applications in medical dressing materials used in wound care and healing. Two antimicrobial proteins lysozyme and hydramacin-1 (HM-1) were surface immobilized through two linkers (3-aminopropyl) triethoxysilane (APTES) and citric acid in the presence of the water soluble carbodiimide coupling reagent 1-cyclohexyl-3-(2-morpholinoethyl)carbodiimide metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Antimicrobial peptides are attractive compared to small organic molecules used as antibiotics [137,138]. Cellulose was modified with several peptides such as gentamicin [139].…”
Section: Antimicrobial Peptides-modified Cellulosementioning
confidence: 99%
“…Antimicrobial peptides are attractive compared to small organic molecules used as antibiotics [137,138]. Cellulose was modified with several peptides such as gentamicin [139].…”
Section: Antimicrobial Peptides-modified Cellulosementioning
confidence: 99%
“…Cotton fibers confirmed good to excellent antimicrobial activities, depending on the bacteria (See Table 5). Then, cotton fibers also can be combined with an antifouling or antibiofilm approach, increasing advantages for biomedical applications [111].…”
Section: Cotton Fibermentioning
confidence: 99%
“…Thus, the strong peaks arise from cotton's C-O-C vibrations. 19 Fig. 2(B) shows the XRD patterns of pristine cotton and aminoalkylsilane graed cotton (14%) at 6 hours, 10 hours, and18 hours.…”
Section: Chemical Structure Analysismentioning
confidence: 99%
“…For instance, Alongi et al 17 demonstrated a hybrid phosphorus-doped silica film grafted cotton surface through sol–gel treatment to improve only thermal and fire stability properties without evaluating wettability and antibacterial properties. While Edwards et al 18 and Xu et al 19 reported citric acid and APTES grafted cotton for antibacterial activity without studying APTES's impact on wettability or flame resistance properties. Agrawal et al 6 proposed a simple, low-cost, eco-friendly method that can enhance only the durability of superhydrophobic antibacterial cotton fabrics by using fluorine-free silane coupling agents as cross-linkers.…”
Section: Introductionmentioning
confidence: 99%